An illusionary prosthetic design for a unilateral cleft palate patient - Bavbek, Andaç Barkin; Culhaoglu, Ahmet Kursad (European Journal of General Dentistry, 2014)
The prosthetic rehabilitation is an important part of the cleft lip and palate therapy assisting orthodontic and orthognathic treatments. Prosthesis does not only help to improve function and aesthetics but also needs to facilitate a better oral health. The aim of this report is to introduce the prosthetic approach of a 21-year-old female unilateral cleft palate patient that considered reinforcing the mobile canine adjacent to the cleft, easing the elimination of dental plaque from the remaining fistula and reaching an accurate occlusion. Facial aesthetics was established by the illusionary effect of a removable crown complex which is joined onto a fixed partial denture with a precision attachment system.
Keywords: Cleft palate; illusionary effect; precision attachment